On some points of the biochemistry of blood, considered as a physical-chemical system in populated highlands of Peru - Monge M., Carlos (1938)
The work of Henderson and his associates on the blood, considered as a physical-chemical system, have established the mathematical functions that integrate the variables that constitute it. Dill, Talbot and Consolazid studied, following these guidelines, the electrolyte balance of man in heaven. In this study, we report the observations we conducted for 10 years.